AEF1/MPR25 is implicated in RNA editing of plastid atpF and mitochondrial nad5, and also promotes atpF splicing in Arabidopsis and rice. (March 2015) - Yap, Aaron; Kindgren, Peter; Colas des Francs‐Small, Catherine; Kazama, Tomohiko; Tanz, Sandra K.; Toriyama, Kinya; Small, Ian
Summary RNA editing is an essential mechanism that modifies target cytidines to uridine in both mitochondrial and plastid mRNA. Target sites are recognized by pentatricopeptide repeat (PPR) proteins. Using bioinformatics predictions based on the code describing sequence recognition by PPR proteins, we have identified an Arabidopsis editing factor required for editing of atpF in plastids. A loss‐of‐function mutation in ATPF EDITING FACTOR 1 (AEF1, AT3G22150) results in severe variegation, presumably due to decreased plastid ATP synthase levels. Loss of editing at the atpF site is coupled with a large decrease in splicing of the atpF transcript, even though the editing site is within an exon and 53 nucleotides distant from the splice site. The rice orthologue of AEF1, MPR25, has been reported to be required for editing of a site in mitochondrial nad5 transcripts, and we confirm that editing of the same site is affected in the Arabidopsis aef1 mutant. We also show that splicing of chloroplast atpF transcripts is affected in the rice mpr25 mutant. AEF1 is thus highly unusual for an RNA editing specificity factor in that it has functions in both organelles.